Assessment of the myocardial area at risk: comparing T2-weighted cardiovascular magnetic resonance imaging with contrast-enhanced cine (CE-SSFP) imaging—a DANAMI3 substudy. (31st July 2018) - Göransson, Christoffer; Ahtarovski, Kiril Aleksov; Kyhl, Kasper; Lønborg, Jacob; Nepper-Christensen, Lars; Bertelsen, Litten; Ghotbi, Adam Ali; Schoos, Mikkel Malby; Køber, Lars; Høfsten, Dan; Helqvist, Steffen; Kelbæk, Henning; et al.
Abstract: Aims: Myocardial salvage following treatment for ST-segment elevation myocardial infarction is prognostic for morbidity and mortality. Studies with myocardial salvage as endpoint rely on valid assessment of the myocardial area at risk (AAR). T2-weighted cardiovascular magnetic resonance (CMR) imaging is the preferred method to assess the AAR. However, T2-weighted imaging can be of poor image quality and uninterpretable. Contrast-enhanced (CE) cine imaging can also show AAR and our aim was to investigate if CE-cine can replace T2-weighted imaging. Cine imaging is part of a standard CMR-protocol and implementing CE-cine imaging for assessment of the AAR would mean shorter investigation time. Methods and results: As a DANAMI-3 substudy, we performed successful dual imaging of the AAR in 166 participants using both T2-weighted short tau inversion recovery (T2-STIR) and CE-cine imaging. T2-STIR imaging was non-diagnostic in nine and CE-cine in one scan during the period. CE-cine measured 4.7% of left ventricle (LV) [95% confidence interval 3.2–6.2%] smaller AAR compared with T2-STIR images ( P < 0.001). Visual analysis of a plot of infarct size vs. AAR showed an overestimation of the AAR when measured with T2-STIR images. There was no difference in AAR with CE-cine in an interobserver analysis of 46 scans [1.2 g (standard deviation 9.5), P = 0.42]. Conclusions: CE-cine imaging shows good internal consistency in assessment of the AAR. A visual inspection reveals possible overestimation of AAR with T2-STIR images. There is good interobserver agreement in the analysis of CE-cine imaging. CE-cine can replace T2-STIR imaging resulting in a more valid assessment of the myocardial AAR.